Neurokinin3-receptors are linked to inositol phospholipid hydrolysis in the guinea-pig ileum longitudinal muscle-myenteric plexus preparation. - Guard, S. (1988)
1. Tachykinin-stimulated inositol phospholipid hydrolysis was examined in slices of longitudinal muscle from guinea-pig ileum. 2. Substance P, neurokinin A and neurokinin B induced a concentration-dependent accumulation of total [3H]-inositol phosphates in the presence of 12 mM lithium with similar maximal responses and EC50 values. 3. The selective NK1-receptor agonist, substance P methyl ester, and the selective NK3-receptor agonist succ-[Asp6, MePhe8]-SP(6-11) (senktide) also stimulated [3H]-inositol phosphate formation with maximum responses of 50.69 +/- 0.96 and 45.64 +/- 1.17% relative to 10 microM substance P, respectively. Substance P methyl ester was approximately equipotent with substance P, whereas senktide was approximately 100 times more potent. 4. When added together, maximally effective concentrations of substance P methyl ester and senktide gave responses that were fully additive. In contrast, responses to substance P and neurokinin B were not additive. 5. The stimulation of [3H]-inositol phosphate formation by substance P, neurokinin B and senktide was not affected by atropine (2 microM) or tetrodotoxin (TTX, 0.3 microM). 6. The contractile effect of senktide was inhibited completely by TTX and partially blocked by atropine. Contractions induced by substance P methyl ester were not changed in the presence of TTX or atropine. 7. [D-Pro4, D-Trp7,9,10]-SP(4-11) competitively antagonized the action of substance P methyl ester on inositol phospholipid hydrolysis and contraction, but had no significant effect on senktide-induced inositol phospholipid breakdown or contraction. 8. These results suggest that NK3-receptors in the guinea-pig ileum are coupled to inositol phospholipid hydrolysis.